Fiscal Independence of the Regional Government of Kupang Regency in the Implementation of Regional Government Affairs - Nakamnanu, Surya Pae Medelson (Formosa Journal of Applied Sciences, 2023)
The financial performance of the Kupang Regency regional government is important information in making regional financial management policies. One tool for analyzing local government financial performance is by analyzing financial ratios. This research aims to analyze the fiscal independence of the Kupang Regency regional government in 2017-2021. This research is a case study research conducted at the Regional Financial and Asset Management Agency. Data collection using interviews and documentation The results of the research show that the degree of fiscal decentralization over the five year period (2017-2021) is on average 7.5% and Fiscal Independence is on average 6.52% which based on the criteria is categorized as very low This means that regional financial capacity to finance its activities is still very lacking and is dependent on the central government.